Steinernema diaprepesi (Rhabditida: Steinernematidae) parasitizing Gonipterus platensis (Coleoptera: Curculionidae) - Damascena, Alixelhe Pacheco [UNESP]; Carvalho, Vanessa Rafaela de [UNESP]; Ribeiro, Murilo Fonseca [UNESP]; Horta, Andre Ballerini [UNESP]; Castro e Castro, Barbara Monteiro de; Vinha Zanuncio, Antonio Jose; Wilcken, Carlos Frederico [UNESP]; Zanuncio, Jose Cola; Siciliano Wilcken, Silvia Renata [UNESP] (Royal Soc, 2020)
Entomopathogenic nematodes (EPNs) can control pests due to mutualistic association with bacteria that reproduce and kill the host from septicemia, making the environment favourable for nematode development and reproduction. The objective of this study was to identify an EPN isolate collected in eucalyptus cultivation and to determine its pathogenicity with regard to Gonipterus platensis Marelli (Coleoptera: Curculionidae). Four steel-mesh traps with two seventh-instar Galleria mellonella larvae were buried 5 cm deep in the soil in a commercial Eucalyptus plantation. After 7 days, the traps were packed in plastic bags and transported to laboratory to isolate the EPNs using White traps. The obtained nematodes were multiplied in G. mellonella larvae and identified by sequencing their D2/D3 expansion of the 28S rDNA region by polymerase chain reaction (PCR) and specific primers for ITS regions. Steinernema diaprepesi was identified and inoculated into G. platensis pupae at doses of 500, 1000 and 5000 infective juveniles (IJs) to determine its pathogenicity to this pest. At 8 days after inoculation, the mortality rate of the G. platensis pupae was 80% with the lowest concentration and 100% with the others. The emergence of nematodes and the rapid degradation of G. platensis pupae were observed in those inoculated with IJs. The pathogenicity to the G. platensis pupae indicates potential for using this nematode in the integrated management of this insect.
Keywords: biological control; eucalyptus weevil; entomopathogenic nematodes; pathogenicity